The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3168/jds.2013-7083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineral content of bovine drinking water: Does iron content affect milk quality?

Abstract: Implications of water chemistry on milk synthesis are not well described yet water is an important nutrient for dairy cattle. High mineral concentrations (>0.3 mg/kg Fe and others) may be associated with natural levels in ground water, contaminating sources, drought conditions, or storage systems. This study evaluated effects of added iron in bovine drinking water on milk composition (Ca, Cu, Fe, P) measured by inductively coupled plasma mass spectrometry and oxidative stability measured by thiobarbituric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 71 publications
0
22
1
Order By: Relevance
“…Concentrations expressed in microgram per liter ND not detected, NC not computable, n number of samples [36]. Deka [37] reported that Cr concentrations in milk is increased by adding Cr to the feed; however, As in drinking water showed a low biological transference to cow milk [34].…”
Section: 93mentioning
confidence: 99%
“…Concentrations expressed in microgram per liter ND not detected, NC not computable, n number of samples [36]. Deka [37] reported that Cr concentrations in milk is increased by adding Cr to the feed; however, As in drinking water showed a low biological transference to cow milk [34].…”
Section: 93mentioning
confidence: 99%
“…In general, it is well known that iron in milk can catalyse lipid oxidation, subsequently leading to rancidity with the development of an unpleasant odour and flavour (Mann et al 2013). In the present study, the main reason for using iron microencapsulation to fortify milk products was the potential of oxidised off-flavours.…”
Section: Tba Test During Storagementioning
confidence: 99%
“…One of the continuing obstacles for the fortification of iron into milk is its catalysis of lipid oxidation during storage and processing (Mann et al . ). In other words, the iron fortification for milk products can produce potential off‐flavours, colour changes and metallic flavours, probably as a result of lipid oxidation of milk fat.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it was reported that the green leafy vegetables cooked in iron utensils demonstrated remarkably higher iron bioavailability than those prepared with stainless steel and aluminum vessels (Kumari et al, 2004). However, the iron ions released from iron utensils were reported to react with food compounds and adversely affect the sensory proprieties of milk, green tea, meat, beer, potatoes, and eggs (Alexandropoulou, Komaitis, & Kapsokefalou, 2006;Griffiths, 1991;Mann, Duncan, Knowlton, Dietrich, & O'keefe, 2013;O'sullivan, Byrne, Stagsted, Andersen, & Martens, 2001). To the best of our knowledge, there was no publication regarding the effects of cooking pots on the sensory and nutritional qualities of pea paste.…”
mentioning
confidence: 99%